3(y – 2) = 2(y – 1) – 3
Answers
Answered by
3
Answer:
Ur answer is in ATTACHMENT.......
...........
Step-by-step explanation:
HaR hAr MAhaDev
Attachments:
![](https://hi-static.z-dn.net/files/d74/1b47b121d9c3d4d288e13db7a15c14bb.jpg)
Answered by
3
Step-by-step explanation:
3(y-2) = 2(y-1) -3
3y-6. = 2(-3y-4)
3y-6. = -6y-8
3y+6y = -8+6
9y. = -2
y. = -2/9
hope this will help you ❤
Similar questions
Science,
5 months ago
Math,
5 months ago
Geography,
11 months ago
Computer Science,
1 year ago
Business Studies,
1 year ago